Comparative Study of Residential Lighting Technologies - Ab Ghani, Sharin; Md Yusoff, Mohd Idris (Penerbit Akademia Baru, 2019)
As the lighting load constituted amount of power in electricity system, improving of efficiency in lighting technology would make a beneficial to consumer, energy provider and environment. Consequently, majority of home lighting manufacturers were competing each other by improving and claiming their product as the best energy efficient lighting product. Knowledge or exposure regarding to lighting technology especially on energy efficiency, power quality and economy are an important issues to give awareness to user before buy or use the lighting product. Therefore in this research study, three types of lighting product such as energy saving incandescent lighting, compact fluorescent lighting (CFL) and solid state lighting (LED) were compared. Comparative parameters were collected from data provided by lighting manufacturer and experimental data conducted in laboratory using power quality meter and lux meter. Hence, these study discussed in term of economy, power and light quality and energy efficiency of the tested lighting product. At the end of this study, the best home lighting technology is determined successfully